Formulation of Slow Release NPK Fertilizer Based on Cassava Starch and Lime Peel Biocomposite for Phosphate and Nitrate Leaching Reduction - Maryam, Wanda Salsabila; Hamidah, Nina (Proceeding International Conference on Religion, Science and Education, 2026)
Excessive nutrient loss from fertilizers is one of the main causes of water pollution and eutrophication in agricultural areas. To address this issue, the development of environmentally friendly Slow Release Fertilizers (SRF) has become increasingly important. Coating techniques can be applied to control the rate of nutrient release from fertilizers. The use of biodegradable coating materials is a top priority to reduce nutrient leaching that can potentially trigger water eutrophication. This study aims to formulate Slow Release Fertilizer (SRF) from NPK fertilizers with a coating matrix based on cassava starch and citric acid from lime peel, and to evaluate the rate of nutrient release behavior. Granular NPK-SRF was prepared by varying the mass composition of cassava starch and lime peel. The nutrient leaching rate was determined using UV-Vis spectrophotometry by measuring the nitrate and phosphate concentration in the leachate. The results showed that the coating mass composition greatly influenced the performance of SRF. The optimal formulation was obtained from a ratio of 78% cassava starch and 22% lime peel, which effectively reduced nitrate and phosphate leaching. This best formulation produced leachate with a NO3- content of only 1.85 ppm and a PO43- content of 0.56 ppm, which was much lower than other variations and the non-coated fertilizers. The findings demonstrate that the optimized cassava starch-lime peel coating matrix is an effective and prospective biodegradable coating materials for controlling phosphate and nitrate leaching and thus reducing the environmental risk of fertilizer application.